The Role of Human Resources in the Information System for the General Plan of Procurement and Non-Tender Procurement at the Binjai Mayor's Office - Irna Permata Sari; Andri Soemitra (Penerbit Jurnal Indonesia, 2022)
Procurement of competitive goods/services has a great response to the country's economy. In particular, within the fiscal policy framework, the procurement of goods/services aims to move the economy, increase employment, increase foreign power, and increase economic growth. The flow of the mechanism for the procurement of state goods/services will be more effective and efficient. Presidential Regulation No. 16 of 2018 requires a mechanism for the procurement of government goods/services based on a digital system. In implementation, it is necessary to look at the role of human resources (HR) in implementing SiRUP and non-tender procurement, especially in the procurement of goods and services for the regional secretariat in the city of Binjai. The research method was carried out by means of interviews and direct observation in the procurement of goods/services section of the secretariat of the mayor of Binjai. While the procurement services for the secretariat of the mayor of Binjai have started to operate but are still in the minimal category in implementation, operators/employees (HR) do not really understand how to run SIRUP because there is very little socialization and training on the implementation of SIRUP, especially in the implementation of e-Procurement and the lack of technical guidance and assistance. in the implementation of SIRUP in the procurement of goods/services.